Why do "teeth" need "voice"? The case of anti‐corruption agencies in three Australian states. Issue 4 (8th March 2019) - Ankamah, Samuel Siebie
Abstract: Interactions between horizontal accountability agencies (e.g., anti‐corruption agencies [ACAs]) and social accountability actors (e.g., journalists, civil society activists, and complainants/whistleblowers) are recognized as important to horizontal agencies' performance, but the reason(s) is not clear. This study therefore explores why horizontal accountability agencies need social accountability actors in performing their functions. The study analyses data from 30 key stakeholders in Australia, including ACAs staff members, social accountability actors, and other observers to report on the specific support roles social actors play to ACAs' activities and operations. Through the conceptual lens of social accountability, evidence show that social actors play four key types of support roles to ACAs' activities and operations: activate ACAs' investigations; "amplify" ACAs' operations; guard ACAs' activities and operations; and defend ACAs' independence and powers. These findings support the need for interactions and, also, affirm the potential for research into how these support roles can better be provided for effective anti‐corruption outcomes. The research is of value to public accountability agencies in Australia, and internationally. Abstract : This paper examines why anti‐corruption agencies (ACAs) need social accountability actors to effectively perform their accountability functions. It shows that social actors play four key support roles to ACAs' activities and operations: activate ACAs' investigations; "amplify" ACAs' operations; guard ACAs' operations; and defend ACAs' independence and powers. The findings are of value to public accountability agencies in Australia and internationally.